2012
DOI: 10.1128/aac.00567-12
|View full text |Cite
|
Sign up to set email alerts
|

Development of Anti-Infectives Using Phage Display: Biological Agents against Bacteria, Viruses, and Parasites

Abstract: The vast majority of anti-infective therapeutics on the market or in development are small molecules; however, there is now a nascent pipeline of biological agents in development. Until recently, phage display technologies were used mainly to produce monoclonal antibodies (MAbs) targeted against cancer or inflammatory disease targets. Patent disputes impeded broad use of these methods and contributed to the dearth of candidates in the clinic during the 1990s. Today, however, phage display is recognized as a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 168 publications
1
70
0
4
Order By: Relevance
“…The phage display technology is a biomolecular tool with applications in basic research and in drug discovery. Ligands identified from the screening of phage-displayed peptide libraries enabled the selection of peptides with an affinity to biologically relevant sites on the surface of the target protein (47,58,59). AniA belongs to the surface-exposed copper nitrite reductases, which are responsible for the reduction of nitrite to nitric oxide under oxygen-limiting conditions and are primarily found in Gram-negative bacteria (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phage display technology is a biomolecular tool with applications in basic research and in drug discovery. Ligands identified from the screening of phage-displayed peptide libraries enabled the selection of peptides with an affinity to biologically relevant sites on the surface of the target protein (47,58,59). AniA belongs to the surface-exposed copper nitrite reductases, which are responsible for the reduction of nitrite to nitric oxide under oxygen-limiting conditions and are primarily found in Gram-negative bacteria (27).…”
Section: Discussionmentioning
confidence: 99%
“…We chose a phage display approach to identify peptide ligands interacting with AniA, as this technology has been successfully applied in basic and translational research and some of the identified peptides are currently in preclinical or clinical trials (47,48). To provide a high diversity of peptide sequences, two commercially available M13 phage-based randomized peptide libraries comprised of 1.9 ϫ 10 9 independent linear dodecameric peptides (Ph.D.-12) and 3.7 ϫ 10 9 heptameric peptides each flanked by a pair of cysteine residues (Ph.D.-C7C) were used (Fig.…”
mentioning
confidence: 99%
“…The common approaches adopted for the development of AMP combinatorial libraries can be broadly divided into molecular biology techniques and solid phase peptide synthesis (SPPS) strategies [63,64]. The former, which relies heavily on the link between the peptide amino acid sequence and the gene encoding it, typically involve the use of phage- [73,74] or ribosome-display systems [75] coupled with selection based on the binding of peptide-phage or peptide-ribosomemRNA complexes to immobilized antibodies or bacterial membranes. The cloning and expression of AMP-encoding oligonucleotide libraries in the periplasmic space of a cellular host also permits rapid and direct screening of active molecules against microbes of interest [76].…”
Section: Bioinformatics and Combinatorial Library Technologiesmentioning
confidence: 99%
“…This technique has been used for diverse number of applications (Hamzeh-Mivehroud et al 2013). In particular the identified peptides represent paratopes (antigen binding site of immunoglobulins) and are considered viable alternative to antibodies, hence can be used to develop better diagnostic and anti-infective applications (Ladner et al 2004;Huang et al 2012). In recent years, phage display method has been used to identify specific peptides for large number of pathogenic viruses including west nile virus (Bai et al 2007), hepatitis C virus (Hong et al 2010), HIV (Welch et al 2010), influenza virus (Wu et al 2011).…”
Section: Introductionmentioning
confidence: 99%